2017
DOI: 10.17161/foec.v32i2.6772
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Enhance Memory Based on Brain-Research

Abstract: Memory is a wonderful trait of human beings. Now, more than ever in history, scientists are unlocking the secrets to enhancing memory. Memory is extremely important to educators, not only for them personally as they age and worry about failing memory, but, most important, for the role that memory plays in the teaching/learning process. Memory, as a concept, often is relegated to a minimal role. As noted by Caine and Caine (1997), "Many of us associate the word memory with the recall of specific dates or facts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 32 publications
3
21
1
1
Order By: Relevance
“…It was suggested that context is an aid for learners to develop and understand unknown words efficiently (Hayati & Shahriari, 2010). This finding actually contradicted the result of the study done by Banikowski and Mehring (1999).…”
Section: Memory Strategy and Vocabulary Retentioncontrasting
confidence: 74%
See 2 more Smart Citations
“…It was suggested that context is an aid for learners to develop and understand unknown words efficiently (Hayati & Shahriari, 2010). This finding actually contradicted the result of the study done by Banikowski and Mehring (1999).…”
Section: Memory Strategy and Vocabulary Retentioncontrasting
confidence: 74%
“…Some of these studies are reviewed in the following. Banikowski and Mehring (1999) did a study on strategies to enhance memory. After analyzing the data, they gave superiority to rehearsal strategy as a traditional vocabulary learning strategy which is used by both learners and teachers.…”
Section: Memory Strategy and Vocabulary Retentionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, a disruption in processing fluency may actually correlate with a greater need to attend to the stimuli for a longer period of time in order to effectively process the information. Because of the importance of attention in memory of students (forreview, see Banikowski& Mehring, ), longer processing times (i.e.,greater attention duration) might actually improve retention of the information being processed.…”
Section: Introductionmentioning
confidence: 99%
“…By the embedded meanings in the proposition, "No true educator simply wants to 'teach'; educators want students to 'learn'" (Banikowski 1999), the teaching paradigm has shifted from emphasising "what students are and how to teach them" to "what teachers do and how to improve them" to the recent, "What students do…" as phrased by Biggs in 1999(Davies 2010 to make meaning of their learning. Within the existing paradigm, teaching activities are to be designed to ensure that students are engaged in meaningful learning, as a measure for bridging the gaps in performance by providing support for the less engaged to move their learning to a higher continuum: to develop the ability to link ideas, remembering them and using the acquired skills and knowledge later on.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%